Prototype Alat Pensterilan Jalur Khusus Transjakarta Menggunakan Module Transmitter Receiver 433 Mhz Berbasis Module Arduino Promini Atmega 328 - Rahmawati, Ita; Pratama, Riski Dwi; Bintoro, Jusuf (LPPM Universitas Negeri Jakarta, 2014)
Prototype Tool sterilizing TransJakarta Using Special Line Module 433 MHz Receiver Transmitter Module Based Promini Arduino Atmega 328 aiming to design and build a device that can help sterilize special line transjakarta. Sterilizing instruments transjakarta special line consists of 433 MHz Receiver Transmitter Module, and Module Arduino Atmega Promini 328. experimental results have successfully created and tested tool sterilizer special line transjakarta can enable